DEVELOPMENT OF TWO MODELS OF DYNAMIC INTEGRATION OF CLOUD COMPUTING RESOURCES WITH ALIEN GRID - A. T. Harutyunyan (ՀՀ ԳԱԱ հրատ.)
The work on enabling one click deployment of CERN ALICE experiment Grid sites on the Infrastructure as a Service cloud is described. Two models of dynamic virtual AliEn Grid site deployment are developed.
Keywords: Technology